Capoterapia: a percep????o dos idosos com rela????o ?? pr??tica da capoterapia e seus benef??cios biopsicossociais - Prazeres, Maria M??rcia Viana (2017)
The aging of the world's population, motivated by the increase in life expectancy reveals, on the one hand, a great achievement of humanity throughout its history and, on the other, represents one of its great challenges. Given the need to make social and economical efforts in the sense of enabling this population a healthy longevity from the physiological, psychological and social point of view. Therefore, it is relevant to the study of the practices that are most appropriate for the elderly, and the study on playful and playfulness make an important contribution because they value activities that are pleasant and meaningful to the elderly. Capotherapy, considered a playful modality, because this is a little known activity, makes of it an interesting object of study. Therefore, the objective of this research was to investigate the perception about the elements which compose the practice of Capotherapy and the effects on the biopsychosocial dimensions in the life of elderly practitioners enrolled in an association of the elderly. The research was exploratory and descriptive, with qualitative and quantitative approach, with the participation of 34 individuals, being 28 women and 6 men, average age of 71 (?? 8 years). Data were collected from a questionnaire applied individually with socioeconomic information and a semi-structured script with two generating questions: "What is Capotherapy for you, in terms of the elements that make it up?" And "How do you see yourself before and after the practice of Capotherapy????. For the analysis of the data, the software IRAMUTEQ- Interface de R pour analyses Multidimensionnelles des Textes et de Questionaires, software Excel 2010 and semi-structured interviews. The results, based on the reports of the elderly, indicated that Capoterapy can be considered a playful practice, according to the elements that compose it, which is associated with corporal practices, capoeira and dance, and which provides positive effects on self-esteem, status functional, the sensation of physical and psychological pain, memory, the rescue of reminiscences, the feeling of belonging and social interaction. It is concluded that the Capotherapy is a corporal practice with playful aspects, that provides several biopsychosocial benefits to the elderly population.